Pengaruh Profitabilitas, Ukuran Perusahaan dan Kepemilikan Institusional Terhadap Pengungkapan Emisi Karbon - Sianturi, Tria Adelina; Aziza, Nurna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study analyzes the effect of profitability, company size, and institutional ownership on the disclosure of carbon emissions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The research population includes all manufacturing entities, with a total of 55 samples obtained through purposive sampling technique. The approach used is quantitative, with multiple linear regression analysis using the help of SPSS version 27. Research data obtained from annual reports and corporate sustainability reports. The results showed that profitability with a significance value of 0.017 < 0.05 and company size with a significance value of 0.029 < 0.05 had a positive effect on the disclosure of carbon emissions. However, institutional ownership with a significance value of 0.361 > 0.05 has no influence on the disclosure of carbon emissions. Although Indonesia has committed to the Net Zero Emission (NZE) target, pressure from institutional investors has not been enough to encourage widespread carbon emission reporting practices. This indicates that environmental transparency in Indonesia is still voluntary and not fully a normative obligation. This research highlights the need for active stakeholder roles and strengthened regulations to make carbon emissions reporting a more common and standardized practice.